2017
DOI: 10.1111/resp.13084
|View full text |Cite
|
Sign up to set email alerts
|

Cough is less common and less severe in systemic sclerosis‐associated interstitial lung disease compared to other fibrotic interstitial lung diseases

Abstract: Cough is more frequent, more severe and more often productive in IPF and chronic HP compared to SSc-ILD, despite similar ILD severity in these cohorts. Cough severity is strongly and independently associated with dyspnoea and pulmonary function, and is a significant contributor to reduced quality of life in both IPF and SSc-ILD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 22 publications
8
38
0
Order By: Relevance
“…Interestingly, Cheng et al . found that burden of cough in HP is very similar to that seen in IPF with 83% and 87% of individuals reporting cough with similar median VAS scores of 29 and 39, respectively.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…Interestingly, Cheng et al . found that burden of cough in HP is very similar to that seen in IPF with 83% and 87% of individuals reporting cough with similar median VAS scores of 29 and 39, respectively.…”
mentioning
confidence: 94%
“…Interestingly, Cheng et al 5 found that burden of cough in HP is very similar to that seen in IPF with 83% and 87% of individuals reporting cough with similar median VAS scores of 29 and 39, respectively. Although the cough burden was also high in scleroderma at 68% with a VAS score of 18, it was significantly less frequent and less intrusive than in HP or IPF.…”
mentioning
confidence: 95%
See 3 more Smart Citations